Development of STEAM-Based Mathematics Teaching Materials on Direct and Inverse Proportion to Improve Mathematical Problem-Solving Ability and Self Regulated Learning (Department of Mathematics, Universitas Negeri Semarang, 2023)
This research was research and development whose product was in the form of teaching materials based on STEAM (Science, Technology, Engineering, Art, and Mathematics). This research and development aims to analyze the feasibility and readability, as well as test the effectiveness of teaching materials in improving problem-solving abilities and Self Regulated Learning (SRL). The development stages include potentials and problems; data collection; product design; design validation and revision; product trials (readability tests) and revisions; trial implementation and revision; and then the final product. Furthermore, this study used a one-group pretest and posttest design, carried out at MTs Al-Utsmani with 37 class VIID students in the 2022/2023 academic year as respondents. The results of this study indicate that the developed STEAM-based teaching materials have a feasibility level of 92.82% with very feasible criteria; legibility level of 63.22% with easy-to-understand criteria; as well as effectively improve problem-solving abilities and SRL. This effectiveness is indicated by the average mathematical problem-solving abilities of students after using teaching materials is more than or equal to the Minimum Completeness Criteria, the mathematical problem-solving ability of students who achieve Minimum Completeness Criteria after using complete teaching materials in a classical manner with a proportion of at least 75%, Improvement of students' mathematical problem-solving abilities after using teaching materials is in the moderate minimal category, average SRL after using teaching materials are in the minimal moderate SRL categories, SRL that is in the minimal moderate SRL category while after using teaching materials complete in a classical manner with a proportion of at least 75%, improvement of SRL after using teaching materials is in the moderate minimal category.